Grouting material for reinforcing coal seam floor and preparation method thereof

By using grouting materials prepared by raw materials such as isocyanate and preparing synergists by treating nano-silica, the problems of poor flame retardancy and low reinforcement strength of polyurethane grouting reinforcement materials are solved, and efficient reinforcement of coal seam base plates and safety guarantees for coal mining operations are achieved.

CN119775520APending Publication Date: 2025-04-08YULIN UNIV
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411947023.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-27
Publication Date
2025-04-08

AI Technical Summary

Technical Problem

The existing polyurethane grouting reinforcement materials have poor flame retardancy and low reinforcement strength, making it difficult to effectively reinforce the coal seam base plate, and there are safety risks of coal mining operations.

Method used

Grouting materials are prepared using raw materials such as isocyanate, polyether polyol, composite catalyst, nanosilica, triphenyl phosphate, p-toluenesulfonic acid, glutamine and dihydromumenol. The nanosilica synergist is prepared by treating nanosilica and fully mixed with isocyanate prepolymer to improve the curing strength and flame retardant properties of the grouting material.

Benefits of technology

The flame retardant and mechanical strength of the grouting materials are significantly improved, the reinforcement performance of the coal seam base plate is enhanced, and the safety hazards of coal mining operations are reduced.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005213909810000101
    Figure BDA0005213909810000101
Patent Text Reader

Abstract

The invention discloses a grouting material for coal seam floor reinforcement and a preparation method thereof, and belongs to the technical field of coal seam mining, the grouting material is prepared from the following raw materials: isocyanate, polyether polyol, a composite catalyst, nano silicon dioxide, triphenyl phosphate, p-toluenesulfonic acid, glutamine, dihydromyrcenol and the like. The preparation method comprises the following steps: treating nano silicon dioxide to prepare a nano silicon dioxide reinforcing agent, preparing an isocyanate prepolymer, adding the nano silicon dioxide reinforcing agent, fully mixing, compounding to prepare the grouting material, and adding the prepared isocyanate prepolymer to prepare the grouting material. According to the present invention, with the addition of the nano-silica reinforcing agent, the heat released during the polyurethane reaction formation can be effectively reduced, the potential safety hazard can be reduced, and the added nano-silica reinforcing agent can effectively improve the fire resistance and the curing strength of the polyurethane formed by curing the grouting material so as to well reinforce the coal seam floor and well ensure the safe coal mining operation.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of coal seam mining, and in particular to a grouting material for reinforcing a coal seam floor and a preparation method thereof. Background Art

[0002] With the large-scale mining of coal resources, the mining environment of coal mines is becoming increasingly complex. As an important supporting structure under the coal seam, the coal seam floor is subjected to tremendous pressure and complex geological stress during the mining process. Many coal mines are facing serious problems such as water inrush from the coal seam floor and deformation and damage of the floor rock strata. These problems not only threaten the safe production of coal mines, but also may lead to a large amount of coal resources being unable to be effectively mined, resulting in resource waste and economic losses. Therefore, grouting reinforcement of the coal mine floor to ensure the safety of coal mining operations and improve mining efficiency is a difficult problem that many coal mines need to solve.

[0003] Traditional cement-based grouting reinforcement materials have the advantages of wide sources and low cost, but they have a long setting time and slow early strength development, making it difficult to provide effective support and reinforcement for the coal seam floor in a short period of time. In addition, the cement particles are large in size and have poor flow permeability, making it difficult to penetrate into the small cracks in the coal seam floor, resulting in poor reinforcement effect. Polyurethane polymer materials have the characteristics of high bonding strength, good mechanical properties, and good slurry fluidity. This polymer can fully bond coal and rock together, so that the broken coal and rock mass can eventually form a whole, thereby enhancing the overall strength of the rock mass, playing a role in rock mass reinforcement, and is conducive to ensuring the safety of coal mining operations. In recent years, polyurethane grouting reinforcement materials have achieved good results in practical applications underground in coal mines. However, the reaction of polyurethane grouting reinforcement materials will release a large amount of heat, and the polyurethane prepared by conventional methods has poor flame retardancy, which can easily cause fire safety accidents. In addition, the coal seam floor, as the supporting structure below, is under tremendous pressure. The reinforcement strength of the polyurethane grouting material prepared by conventional methods is insufficient, which will cause the coal seam floor to be unable to support the overlying rock pressure or mining pressure, posing a major operational safety hazard.

[0004] Therefore, there is a need to find a coal seam floor grouting reinforcement material with high curing strength and good flame retardant properties to improve the reinforcement strength of the coal seam floor, reduce heat release during the grouting process, and effectively reinforce the coal seam floor to ensure the safety of coal mining operations. Summary of the invention

[0005] In view of this, the purpose of the present invention is to provide a grouting material for coal seam floor reinforcement and a preparation method thereof, so as to solve the problems of poor flame retardancy and low reinforcement strength of conventional polyurethane grouting reinforcement materials, improve the reinforcement performance of coal seam floors, and promote the safe conduct of coal mining operations.

[0006] The present invention solves the above technical problems by the following technical means:

[0007] A grouting material for reinforcing a coal seam floor, the grouting material comprising the following raw materials:

[0008] Isocyanate, polyether polyol, composite catalyst, nano-silica, triphenyl phosphate, p-toluenesulfonic acid, glutamine, dihydromyrcenol.

[0009] Furthermore, the composite catalyst is obtained by mixing stannous octoate and triethylenediamine in a mass ratio of 2:1.

[0010] The present invention also discloses a preparation method of the grouting material, and the specific preparation method is as follows:

[0011] (1) adding nano-silica to anhydrous ethanol and stirring to disperse, then dissolving triphenyl phosphate in acetone and adding it, then adding p-toluenesulfonic acid, heating to 80-90° C. to react for 4-6 hours, filtering and removing the filtrate after the reaction is completed, washing with clean water and drying to obtain phosphorus-containing nano-silica;

[0012] (2) adding phosphorus-containing nano-silica to water and stirring to disperse, adding glutamine and heating to 50-60° C. and stirring to react for 2-4 hours, then dissolving dihydromyrcenol in ethanol and adding it to continue to react at 50-60° C. for 1-2 hours, then heating to 70-80° C. and reacting for 30-60 minutes, cooling to room temperature after the reaction is completed and standing overnight, then filtering to remove the filtrate, washing with clean water and drying to obtain a nano-silica synergist;

[0013] (3) drying the polyether polyol at 110° C. for 2 h to obtain a dehydrated polyether polyol, cooling the temperature to 60-65° C., adding isocyanate and a composite catalyst, and then heating the temperature to 70-80° C. for reaction for 2-3 h to obtain an isocyanate prepolymer; adding a nano-silica synergist to the isocyanate prepolymer, and reacting at a high speed with stirring to obtain component A;

[0014] (4) taking a polyether polyol, adding a composite catalyst, stirring and mixing uniformly to obtain component B; adding component A to component B and mixing uniformly to obtain a grouting material.

[0015] The invention processes nano silicon dioxide to prepare a nano silicon dioxide reinforcing agent, and then fully mixes and reacts the nano silicon dioxide reinforcing agent with an isocyanate prepolymer to prepare a grouting material, so as to better improve the flame retardancy and mechanical strength of polyurethane formed by curing the grouting material, which is beneficial to better ensure the safety of coal mining operations.

[0016] Specifically, the present invention uses triphenyl phosphate and nano-silica for heating reaction, so that triphenyl phosphate is grafted onto nano-silica to obtain phosphorus-containing nano-silica, and when added to the grouting material, phosphorus and silicon can synergistically enhance the flame retardant effect, and the overall flame retardancy of the polyurethane is improved by treating the silica. Compared with directly mixing the flame retardant into the grouting material, the problem of reduced flame retardant performance caused by the chemical bond breakage of the flame retardant caused by the pressure of high-pressure grouting during coal seam floor reinforcement can be reduced; further, glutamine and dihydromyrcenol are added in sequence to heat the phosphorus-containing nano-silica to obtain a nano-silica reinforcing agent. In this process, glutamine changes the surface of the nano-silica Properties, enhance the chemical bonding ability and intermolecular interaction force between nano-silica and isocyanate prepolymer, thereby promoting better bonding of nano-silica to isocyanate prepolymer, increasing the cross-linking density of polyurethane formed by grouting, and enhancing the curing strength; however, the toughness of the polyurethane with effectively enhanced cross-linking density will be reduced, and the tensile strength will be reduced, which will easily lead to cracks and weaken the reinforcement effect. Dihydromyrcenol further reacts and bonds to the nano-silica treated with glutamine, forming a chain structure with good folding ability covering the surface of the nano-silica, thereby ensuring the curing strength of the polyurethane while ensuring good flexibility, inhibiting the appearance of cracks in the coal seam floor after reinforcement, and having good comprehensive performance.

[0017] Furthermore, in the step (1), the mass ratio of nano-silicon dioxide, triphenyl phosphate and p-toluenesulfonic acid is (0.2-0.35): (0.02-0.04): (0.005-0.01).

[0018] Furthermore, in the step (2), the mass ratio of phosphorus-containing nano-silicon dioxide, glutamine and dihydromyrcenol is (0.15-0.3): (0.03-0.04): (0.02-0.03).

[0019] Furthermore, in the step (3), when preparing component A, the mass ratio of polyether polyol, isocyanate, composite catalyst and nano-silicon dioxide synergist is (1-2.5): (1-2.5): (0.01-0.02): (0.1-0.25).

[0020] Furthermore, in step (3), the high-speed stirring reaction speed is 800-1000 r / min, and the stirring time is 2-3 h.

[0021] Furthermore, in the step (4), when preparing component B, the mass ratio of polyether polyol to composite catalyst is (1-2): (0.005-0.01).

[0022] Furthermore, the mass ratio of component A to component B is (2-5):(1-2).

[0023] Beneficial effects:

[0024] 1. The present invention first uses polyether polyol and isocyanate to prepare isocyanate prepolymer and mixes them to prepare grouting material, which can reduce the heat released by the curing reaction of the grouting material to a limited extent and has better safety performance.

[0025] 2. The present invention prepares a nano-silicon dioxide synergist by treating nano-silicon dioxide, and mixes the nano-silicon dioxide synergist with isocyanate prepolymer after sufficient dispersion reaction to prepare grouting. The nano-silicon dioxide synergist can effectively improve the curing strength and flame retardant properties of polyurethane formed by curing the grouting material. In addition, under this method, the nano-silicon dioxide can be evenly dispersed in the isocyanate prepolymer after high-speed stirring reaction, thereby promoting the uniform dispersion of the nano-silicon dioxide in the grouting material, better exerting its performance, and preparing a grouting material with strong flame retardancy and good mechanical properties, which is conducive to better ensuring the safe conduct of coal mining operations. DETAILED DESCRIPTION

[0026] The present invention will be described in detail below with reference to specific embodiments:

[0027] Example 1: Preparation of grouting material

[0028] (1) adding 0.3 kg of nano-silica to 3 kg of anhydrous ethanol and stirring to disperse, then dissolving 0.03 kg of triphenyl phosphate in 0.3 kg of acetone and adding the mixture, and then adding 0.007 kg of p-toluenesulfonic acid, heating to 85° C. and reacting for 5 h. After the reaction is completed, filtering and removing the filtrate, washing with clean water and drying at 60° C. to obtain phosphorus-containing nano-silica;

[0029] (2) adding 0.25 kg of phosphorus-containing nano-silica to 2.5 kg of water and stirring to disperse, adding 0.035 kg of glutamine and heating to 55° C. and stirring to react for 3 h, then dissolving 0.025 kg of dihydromyrcenol in 0.25 kg of anhydrous ethanol and adding the mixture to continue reacting at 55° C. for 1.5 h, then heating to 75° C. and reacting for 45 min, cooling to room temperature after the reaction is completed and standing overnight, then filtering to remove the filtrate, washing with clean water and drying at 70° C. to obtain a nano-silica synergist;

[0030] (3) drying 2 kg of polyether polyol at 110° C. for 2 h to obtain dehydrated polyether polyol, cooling to 60° C., adding 2 kg of isocyanate and 0.015 kg of composite catalyst, and then heating to 75° C. for reaction for 2.5 h to obtain isocyanate prepolymer; adding 0.2 kg of nano-silica synergist to the isocyanate prepolymer, stirring and reacting at a speed of 900 r / min for 2.5 h to obtain component A;

[0031] (4) 1.5 kg of polyether polyol was taken, and 0.007 kg of composite catalyst was added, and the mixture was stirred and mixed evenly to obtain component B; component A was added to component B in a mass ratio of component A: component B = 2:1, and the mixture was mixed evenly to obtain a grouting material.

[0032] Example 2: Preparation of grouting material II

[0033] (1) adding 0.2 kg of nano-silica to 2 kg of anhydrous ethanol and stirring to disperse, then dissolving 0.02 kg of triphenyl phosphate in 0.2 kg of acetone and adding the solution, and then adding 0.005 kg of p-toluenesulfonic acid, heating to 80° C. and reacting for 6 h. After the reaction is completed, filtering and removing the filtrate, washing with clean water and drying at 60° C. to obtain phosphorus-containing nano-silica;

[0034] (2) adding 0.15 kg of phosphorus-containing nano-silica to 1.5 kg of water and stirring to disperse, adding 0.03 kg of glutamine and heating to 50° C. and stirring to react for 4 h, then dissolving 0.02 kg of dihydromyrcenol in 0.2 kg of anhydrous ethanol and adding the mixture to continue reacting at 50° C. for 2 h, then heating to 70° C. and reacting for 60 min, cooling to room temperature after the reaction is completed and standing overnight, then filtering to remove the filtrate, washing with clean water and drying at 70° C. to obtain a nano-silica synergist;

[0035] (3) drying 1 kg of polyether polyol at 110° C. for 2 h to obtain dehydrated polyether polyol, cooling to 60° C., adding 1 kg of isocyanate and 0.01 kg of composite catalyst, and then heating to 70° C. for reaction for 3 h to obtain isocyanate prepolymer; adding 0.1 kg of nano-silica synergist to the isocyanate prepolymer, stirring and reacting at a speed of 800 r / min for 3 h to obtain component A;

[0036] (4) Take 1 kg of polyether polyol, add 0.005 kg of composite catalyst, stir and mix evenly to obtain component B; add component A to component B in a mass ratio of component A: component B = 2:1, mix evenly to obtain grouting material.

[0037] Example 3: Preparation of grouting material

[0038] (1) adding 0.35 kg of nano-silica to 3.5 kg of anhydrous ethanol and stirring to disperse, then dissolving 0.04 kg of triphenyl phosphate in 0.4 kg of acetone and adding the resulting mixture, and then adding 0.01 kg of p-toluenesulfonic acid, heating the mixture to 90° C. and reacting for 6 h. After the reaction is complete, filtering and removing the filtrate, washing with clean water, and drying the mixture to obtain phosphorus-containing nano-silica;

[0039] (2) adding 0.3 kg of phosphorus-containing nano-silica to 3 kg of water and stirring to disperse, adding 0.04 kg of glutamine and heating to 60° C. and stirring to react for 2 h, then dissolving 0.03 kg of dihydromyrcenol in 0.3 kg of anhydrous ethanol and adding the mixture to continue reacting at 60° C. for 1 h, then heating to 80° C. and reacting for 30 min, cooling to room temperature after the reaction is completed and standing overnight, then filtering to remove the filtrate, washing with clean water and drying at 70° C. to obtain a nano-silica synergist;

[0040] (3) drying 2.5 kg of polyether polyol at 110° C. for 2 h to obtain dehydrated polyether polyol, cooling to 65° C., adding 2.5 kg of isocyanate and 0.02 kg of composite catalyst, and then heating to 80° C. for reaction for 2 h to obtain isocyanate prepolymer; adding 0.25 kg of nano-silica synergist to the isocyanate prepolymer, stirring and reacting at a speed of 1000 r / min for 2 h to obtain component A;

[0041] (4) taking 2 kg of polyether polyol, adding 0.01 kg of composite catalyst and stirring to mix evenly to obtain component B; adding component A to component B in a mass ratio of component A: component B = 5:2 and mixing evenly to obtain a grouting material.

[0042] Comparative Example 1: Preparation of grouting materials

[0043] In contrast to Example 1, the only difference is that the grouting material in Comparative Example 1 lacks step (1) when preparing the grouting material, and triphenyl phosphate is not used to treat the nano-silicon dioxide. The details are as follows:

[0044] (1) adding 0.25 kg of nano-silicon dioxide to 2.5 kg of water and stirring to disperse, adding 0.035 kg of glutamine and heating to 55° C. and stirring to react for 3 h, then dissolving 0.025 kg of dihydromyrcenol in 0.25 kg of anhydrous ethanol and adding the mixture to continue reacting at 55° C. for 1.5 h, then heating to 75° C. and reacting for 45 min, cooling to room temperature after the reaction is completed and standing overnight, then filtering to remove the filtrate, washing with clean water and drying at 70° C. to obtain a nano-silicon dioxide synergist;

[0045] (2) Same as step (3) of Example 1;

[0046] (3) Same as step (4) in Example 1.

[0047] Comparative Example 2: Preparation of grouting materials

[0048] In contrast to Example 1, the only difference is that in the preparation of the grouting material in Comparative Example 2, glutamine is not used to treat the nano-silicon dioxide in step (2), as shown below:

[0049] (1) Same as Example 1;

[0050] (2) adding 0.25 kg of phosphorus-containing nano-silica to 2.5 kg of water and stirring to disperse, dissolving 0.025 kg of dihydromyrcenol in 0.25 kg of anhydrous ethanol and adding the mixture to react at 55° C. for 1.5 h, then heating to 75° C. for 45 min, cooling to room temperature after the reaction is completed and standing overnight, then filtering to remove the filtrate, washing with clean water and drying at 70° C. to obtain a nano-silica synergist;

[0051] (3)~(4) are the same as Example 1.

[0052] Comparative Example 3: Preparation of grouting materials

[0053] In contrast to Example 1, the only difference is that in the preparation of the grouting material in Comparative Example 3, dihydromyrcenol is not used to treat the nano-silicon dioxide in step (2), as shown below:

[0054] (1) Same as Example 1;

[0055] (2) adding 0.25 kg of phosphorus-containing nano-silicon dioxide to 2.5 kg of water and stirring to disperse, adding 0.035 kg of glutamine and heating to 55 ° C. and stirring to react for 3 hours, cooling to room temperature after the reaction is completed and standing overnight, then filtering to remove the filtrate, washing with clean water and drying at 70 ° C. to obtain a nano-silicon dioxide synergist;

[0056] (3)~(4) are the same as Example 1.

[0057] Comparative Example 4: Preparation of grouting materials

[0058] In contrast to Example 1, the only difference is that in Comparative Example 4, the grouting material preparation lacks step (1) and step (2), that is, the nano-silicon dioxide is not processed, and conventional nano-silicon dioxide is directly added in step (3), as shown below:

[0059] (1) drying 2 kg of polyether polyol at 110° C. for 2 h to obtain dehydrated polyether polyol, cooling to 60° C., adding 2 kg of isocyanate and 0.015 kg of composite catalyst, and then heating to 75° C. for reaction for 2.5 h to obtain isocyanate prepolymer; adding 0.2 kg of nano-silicon dioxide to the isocyanate prepolymer, stirring and reacting at a speed of 900 r / min for 2.5 h to obtain component A;

[0060] (2) Same as step (4) in Example 1.

[0061] Comparative Example 5: Preparation of grouting materials

[0062] In contrast to Example 1, the only difference is that in Comparative Example 5, when preparing the grouting material, the nano-silicon dioxide synergist is not added to component A in step (3), but is added to component B in step (4), as shown below:

[0063] (1) to (2) are the same as in Example 1;

[0064] (3) drying 2 kg of polyether polyol at 110° C. for 2 h to obtain dehydrated polyether polyol, cooling to 60° C., adding 2 kg of isocyanate and 0.015 kg of composite catalyst, and then heating to 75° C. for reaction for 2.5 h to obtain isocyanate prepolymer, i.e., component A;

[0065] (4) taking 1.5 kg of polyether polyol, adding 0.007 kg of composite catalyst and 0.2 kg of nano-silicon dioxide synergist, stirring and mixing evenly to obtain component B; adding component A to component B in a mass ratio of component A: component B = 2:1, and mixing evenly to obtain a grouting material;

[0066] Comparative Example 6: Preparation of grouting materials

[0067] In contrast to Example 1, the only difference is that in Comparative Example 6, no nano-silicon dioxide synergist is added during the preparation of the grouting material, as shown below:

[0068] (1) drying 2 kg of polyether polyol at 110° C. for 2 h to obtain dehydrated polyether polyol, cooling to 60° C., adding 2 kg of isocyanate and 0.015 kg of composite catalyst, and then heating to 75° C. for reaction for 2.5 h to obtain isocyanate prepolymer, i.e., component A;

[0069] (2) taking 1.5 kg of polyether polyol, adding 0.007 kg of composite catalyst, stirring and mixing evenly to obtain component B; adding component A to component B in a mass ratio of component A: component B = 2:1, and mixing evenly to obtain a grouting material;

[0070] Experiment: Grouting material performance test experiment

[0071] 1. The properties of the grouting materials of Example 1 and Comparative Examples 1 to 6 were respectively tested, including oxygen index, maximum reaction temperature, compressive strength, and tensile strength, and the obtained data are shown in Table 1.

[0072] Table 1

[0073]

[0074] According to the data analysis in Table 1:

[0075] (1) The grouting material prepared by the present invention has good performance, with a maximum reaction temperature of 78°C, an oxygen index of 29.5%, a compressive strength of 55.3Mpa, and a tensile strength of 5.81Mpa, which can well meet the requirements of various indicators in the AQ / T1089-2020 standard, especially having a significant effect on improving the compressive strength, and has good application prospects in coal seam floor reinforcement.

[0076] (2) In the preparation of the grouting material in Comparative Example 1 of the present invention, triphenyl phosphate was not used to treat the nano-silica. Although the nano-silica had a certain heat resistance, it failed to play a synergistic role, the oxygen index was significantly reduced, and the flame retardancy was poor; in Comparative Example 2, glutamine was not used to treat the nano-silica in the preparation of the grouting material, the interaction force between the nano-silica and the isocyanate prepolymer was poor, thereby reducing the cross-linking density, resulting in a decrease in compressive strength; in Comparative Example 3, dihydromyrcenol was not used to treat the nano-silica in the preparation of the grouting material, which reduced the tensile strength; in Comparative Example 5, the nano-silica synergist was added to component B and then mixed to prepare the grouting material. The nano-silica had poor binding properties with the isocyanate prepolymer and reduced dispersibility in the grouting material, thereby affecting the performance of the grouting material.

[0077] The above embodiments are only used to illustrate the technical solutions of the present invention and are not intended to limit the present invention. Although the present invention is described in detail with reference to the preferred embodiments, it should be understood by those skilled in the art that the technical solutions of the present invention may be modified or replaced by equivalents without departing from the purpose and scope of the technical solutions of the present invention, which should be included in the scope of the claims of the present invention. The techniques, shapes, and structural parts not described in detail in the present invention are all known technologies.

Claims

1. A grouting material for coal seam floor reinforcement, characterized in that: The grouting material comprises the following raw materials: Isocyanate, polyether polyol, composite catalyst, nano-silica, triphenyl phosphate, p-toluenesulfonic acid, glutamine, dihydromyrcenol.

2. The grouting material for coal seam floor reinforcement according to claim 1, characterized in that: The composite catalyst is obtained by mixing stannous octoate and triethylenediamine in a mass ratio of 2:

1.

3. A method for preparing a grouting material for reinforcing a coal seam floor, characterized in that: The preparation method is as follows: (1) adding nano-silica to anhydrous ethanol and stirring to disperse, then dissolving triphenyl phosphate in acetone and adding it, then adding p-toluenesulfonic acid, heating to 80-90° C. to react for 4-6 hours, filtering and removing the filtrate after the reaction is completed, washing with clean water and drying to obtain phosphorus-containing nano-silica; (2) adding phosphorus-containing nano-silica to water and stirring to disperse, adding glutamine and heating to 50-60° C. and stirring to react for 2-4 hours, then dissolving dihydromyrcenol in ethanol and adding it to continue to react at 50-60° C. for 1-2 hours, then heating to 70-80° C. and reacting for 30-60 minutes, cooling to room temperature after the reaction is completed and standing overnight, then filtering to remove the filtrate, washing with clean water and drying to obtain a nano-silica synergist; (3) drying the polyether polyol at 110° C. for 2 h to obtain a dehydrated polyether polyol; cooling the polyether polyol to 60-65° C., adding isocyanate and a composite catalyst, and then heating the polyether polyol to 70-80° C. for 2-3 h to obtain an isocyanate prepolymer; adding a nano-silica synergist to the isocyanate prepolymer, and reacting the mixture with high-speed stirring to obtain component A; (4) taking a polyether polyol, adding a composite catalyst, stirring and mixing uniformly to obtain component B; adding component A to component B and mixing uniformly to obtain a grouting material.

4. The method for preparing a grouting material for coal seam floor reinforcement according to claim 3, characterized in that: In the step (1), the mass ratio of nano-silicon dioxide, triphenyl phosphate and p-toluenesulfonic acid is (0.2-0.35): (0.02-0.04): (0.005-0.01).

5. The method for preparing a grouting material for reinforcing a coal seam floor according to claim 4, characterized in that: In the step (2), the mass ratio of phosphorus-containing nano-silicon dioxide, glutamine and dihydromyrcenol is (0.15-0.3): (0.03-0.04): (0.02-0.03).

6. The method for preparing a grouting material for reinforcing a coal seam floor according to claim 5, characterized in that: In the step (3), when preparing component A, the mass ratio of polyether polyol, isocyanate, composite catalyst and nano-silicon dioxide synergist is (1-2.5): (1-2.5): (0.01-0.02): (0.1-0.25).

7. The method for preparing a grouting material for coal seam floor reinforcement according to claim 6, characterized in that: The high-speed stirring reaction speed in step (3) is 800-1000 r / min, and the stirring time is 2-3 h.

8. The method for preparing a grouting material for reinforcing a coal seam floor according to claim 7, characterized in that: In the step (4), when preparing component B, the mass ratio of polyether polyol to composite catalyst is (1-2): (0.005-0.01).

9. The method for preparing a grouting material for reinforcing a coal seam floor according to claim 8, characterized in that: The mass ratio of component A to component B in the step (4) is (2-5):(1-2).

Citation Information

Cited By

  • Reinforcing grouting material for mine and preparation method of reinforcing grouting material

    CN122167129A